ANALISIS PENGGUNAAN MEDIA INTERAKTIF DALAM PEMBELAJARAN SENI MUSIK TRADISIONAL PADA SISWA KELAS IV SEKOLAH DASAR - Cantika Sri Agustin; Ghevira Aulia Rahima; Shifa Aulia Sabna; Auliya; Tiara Denta Natsyah; Teten Ginanjar Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Advances in digital technology have spurred the use of interactive media in more innovative and student-centered learning; however, its application in the teaching of traditional music in elementary schools remains suboptimal. This study aims to analyze the implementation of interactive media and its impact on the engagement and understanding of fourth-grade students. The study employs a descriptive qualitative approach using a literature review method, with data sources consisting of scientific literature from 2020–2026 analyzed using content analysis techniques. The results indicate that interactive media such as audiovisual materials, animations, and digital applications can enhance student engagement, comprehension, and motivation, as well as create a more engaging and meaningful learning environment. In conclusion, interactive media play a crucial role in improving the quality of traditional music education in elementary schools.